Taxation of Oil Products and GDP Dynamics of Oil-rich Countries - Julien Daubanes (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
This article proposes a complementary explanation for why oil-rich economies have experienced a relative low GDP growth over the last decades: the proportion of taxes in the prices of petroleum products have been globally increasing for the four last decades, thus making oil revenues grow slower than output from manufacturing and yielding a low growth of oil-exporting countries' GDPs. This is illustrated in a two-country model of oil depletion examining why a net oil-exporting country and a net oil-importing country are differently affected by increasing taxes on the resource use. The hypothesis is constructed on the theory of non-renewable resources taxation. The argument is based on the distributional effects of taxes on exhaustible resources, that are mainly borne by the suppliers. The theoretical predictions are not invalidated when put up against available statistics.
Keywords: Q3; O4; F4; 330; Oil curse; Non-renewable resources; Taxes; Oil revenues; GDP; Erdölvorkommen; Wirtschaftswachstum; Mineralölsteuer; Steuereinnahmen; Makroökonomik; OPEC-Staaten